Different scales and integration of data in reservoir simulation - Hartanto, Lina (Curtin University, 2004)
The term upscaling and determination of pseudo curves, or effective parameters, used on a coarse-scale simulation grid are related to the complex and extensive problems associated with reservoir studies. The primary strategy mainly focuses on having a good physical and practical understanding of the particular processes in question, and an appreciation of reservoir model sensitivities. Thus the building of the reservoir simulation models can be optimally determined.By concentrating on the modelling and upscaling gas injection for Enhanced Oil Recovery (EOR) process, which includes Interfacial Tension (IFT) and the amicability effect, a new effective and efficient algorithm of upscaling will be investigated and determined by using several upscaled parameters. The sensitivities of these determined coarse scale parameters (i.e. porosity, absolute and relative permeability and capillary pressure), will also be studied through a history matching of the existing field.